Evaluating the Use of Bortezomib and Eculizumab in Desensitization of Transplant Patients. (February 2014) - Kwiatkowski, Matthew; Welch, Patrick; McComb, Jennifer; Shepler, Brian
Objective : To systematically review the existing literature concerning the utilization of bortezomib and eculizumab to determine if there is enough evidence to warrant their routine use in desensitization protocols for high-risk transplant candidates.Data Sources : PubMed, Google Scholar, and ClinicalTrials.gov were searched using the terms bortezomib, eculizumab, desensitization, transplant, highly-sensitized, pre-sensitized, and antibody-mediated rejection (AMR). The articles included were published between January 2009 and August 2012.Study Selection and Data Extraction : All English-language articles involving human subjects were assessed for inclusion. The search included articles evaluating the use of these agents in desensitization and the prevention of AMR, but excluded articles investigating these drugs in the treatment of established AMR.Data Synthesis : Highly sensitized transplant candidates are at an increased risk of developing AMR after transplant; desensitization potentially reduces this risk. The addition of bortezomib and eculizumab to current desensitization protocols may enhance outcomes. The bortezomib search produced 3 efficacy trials, 1 safety trial, 2 in-progress trials, 14 patient cases from 8 published case reports, and 3 efficacy study abstracts.Conclusions : Much of the available literature assessing the efficacy of bortezomib and eculizumab for use in desensitization exists as restricted clinical trials and incomplete case reports. Bortezomib and eculizumab appear to be potentially effective additions to current desensitization protocols. However, we are unable to determine at this time whether these agents improve the most clinically relevant outcome of successful transplantation. Further well-designed clinical trials are needed to determine their true clinical efficacy in highly sensitized transplant candidates.